Volar Locking Plate Fixation of Distal Radius Fractures: Splint versus Immediate Mobilization - Duprat, André; Diaz, Juan José Hidalgo; Vernet, Paul; Gouzou, Stéphanie; Facca, Sybille; Igeta, Yuka; Liverneaux, Philippe (Journal of Wrist Surgery, 2018)
Background The goal of this study was to demonstrate that the use of a splint after performing an osteosynthesis of the distal radius with a volar locking plate is unnecessary. The main hypothesis was that postoperative flexion of the wrist was greater without a splint. Secondary hypothesis was that patients who were allowed immediate mobilization got better results in terms of pain, Quick Disabilities of the Arm, Shoulder and Hand (DASH), Patient-Rated Wrist Evaluation (PRWE), strength, extension, pronation, and supination.Case Description Our series included 72 patients, aged 59 years in average of which 59 were female patients. All patients had been operated for a volar locking plate fixation of a distal radius fracture. The first 36 patients (group I) were immobilized by a splint at 30° of extension of the wrist for 2 weeks. The following 36 patients (group II) were not immobilized.Results At 3 months, all the average variables were better in the group without splint (group I: flexion 74.83%, extension 83.13%, pronation 92.07%, supination 88.11%, pain 1.72/10, Quick DASH 21.78/100, PRWE 22.97/100, strength 62.96%; group II: flexion 85.50%, extension 83.4%, pronation 92.96%, supination 92.96%, pain 1.28/10, Quick DASH 19.57/100, PRWE 20.56/100, strength 66.34%). No complication was reported.Conclusion Overall, our results demonstrate that wearing a splint after volar locking plate fixation of a distal radius fracture is unnecessary.
Keywords: volar plate; distal radius fractures; splint; mobilization